1999
DOI: 10.1103/physrevc.60.054906
|View full text |Cite
|
Sign up to set email alerts
|

Baryon stopping and hyperon enhancement in the improved dual parton model

Abstract: We present an improved version of the dual parton model which contains a new realization of the diquark breaking mechanism of baryon stopping. We reproduce in this way the net baryon yield in nuclear collisions. The model, which also considers strings originating from diquark-antidiquark pairs in the nucleon sea, reproduces the observed yields of p and Λ and their antiparticles and underestimates cascades by less than 50 %. However, Ω's are underestimated by a factor five. Agreement with data is restored by fi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
71
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(76 citation statements)
references
References 42 publications
5
71
0
Order By: Relevance
“…8 [16,10] by a mechanism of color ropes which consider fusion of strings; also in the Ultra Relativistic Quantum Molecular Dynamics model [17] and in the HIJING model [18] by using an ad hoc multiplicative factor in the string tension. Also the Dual Parton Model [14], considering the possibility of creation of diquark-antidiquark pairs in the nucleon sea, together with the inclusion of diagrams which take into account baryon junction migration [49,50,51], can reproduce the experimental data (for Ω's some rescattering has still to be added). The string fusion is the main ingredient to obtain an enhancement ofΛ production and also to reproduce the Ξ data.…”
Section: Proton-nucleus and Nucleus-nucleus Collisionsmentioning
confidence: 93%
See 2 more Smart Citations
“…8 [16,10] by a mechanism of color ropes which consider fusion of strings; also in the Ultra Relativistic Quantum Molecular Dynamics model [17] and in the HIJING model [18] by using an ad hoc multiplicative factor in the string tension. Also the Dual Parton Model [14], considering the possibility of creation of diquark-antidiquark pairs in the nucleon sea, together with the inclusion of diagrams which take into account baryon junction migration [49,50,51], can reproduce the experimental data (for Ω's some rescattering has still to be added). The string fusion is the main ingredient to obtain an enhancement ofΛ production and also to reproduce the Ξ data.…”
Section: Proton-nucleus and Nucleus-nucleus Collisionsmentioning
confidence: 93%
“…As discussed for strangeness enhancement, it has been pointed out that baryon junction migration [49,50,51] will enhance the stopping power due to diagrams additional to the usual ones of the Dual Parton Model. The inclusion of these diagrams also explains the SPS data.…”
Section: Proton-nucleus and Nucleus-nucleus Collisionsmentioning
confidence: 99%
See 1 more Smart Citation
“…• Diquark breaking and sea-diquarks: A new version of the dual parton model, featuring an improved diquark breaking mechanism has been applied to explain the observed strangeness enhancement at the full SPS energy [19]. Here, the strange-and antibaryon production invokes strings originating from diquark-antidiquark pairs in the nucleon sea to reproduces the observed yields of p and Lambda and their antiparticles.…”
Section: Lbnl-preprint: Lbnl-46167mentioning
confidence: 99%
“…It was found that Baryon junctionanti-junction (J anti-J) loops can indeed enhance anti-Lambda, anti-Xi, anti-Omega yields at SPS energies. While this mechanism leads to a reasonable description of central interactions, it can not explain the enhancement in the measured hyperon to anti-hyperon ratios with increasing centrality.• Diquark breaking and sea-diquarks: A new version of the dual parton model, featuring an improved diquark breaking mechanism has been applied to explain the observed strangeness enhancement at the full SPS energy [19]. Here, the strange-and antibaryon production invokes strings originating from diquark-antidiquark pairs in the nucleon sea to reproduces the observed yields of p and Lambda and their antiparticles.…”
mentioning
confidence: 99%